2018
DOI: 10.1016/j.anai.2018.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the manufacturer-dependent differences in specific immunoglobulin E results for indoor allergens

Abstract: Even though these results are promising, future EQAs have to be closely monitored to ensure this positive trend is not just a snapshot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This pointed to a satisfyingly high degree of precision in the manual analyses. Nevertheless, the good results of the heterogenous in-house collective showed that differences in manual approaches do not have as high of an impact on the general interlaboratory comparability as INSTAND previously found for in vitro allergy diagnostic immunoassays [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 84%
“…This pointed to a satisfyingly high degree of precision in the manual analyses. Nevertheless, the good results of the heterogenous in-house collective showed that differences in manual approaches do not have as high of an impact on the general interlaboratory comparability as INSTAND previously found for in vitro allergy diagnostic immunoassays [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 84%
“…In this context, if should be noted that a certain variability between different methods (and laboratories) is expected, as was recently observed. 71,72 There are a large number of singleplexed diagnostics systems in the world, and four major ones can be identified (Table 15). Each has specific characteristics and performances.…”
Section: Singleplex Assaymentioning
confidence: 99%
“…25,26 Different laboratories performing allergy testing can report variable results for the same patient. 27 Finally, manufacturer differences in allergens can lead to variable serum reactivity, 10 and although the tests used in our study have been validated in dogs, 28,29…”
Section: Discussionmentioning
confidence: 96%
“…9 For example, manufacturer differences in the development of allergen extracts remains a challenge to standardized testing. 10 Testing methodologies differ and include quantification of IgE using FceR1a-based ELISA, polyclonal antibody testing, and enzyme immunometric methodology.…”
Section: Introductionmentioning
confidence: 99%